Application of Microfluidics in Detection of Circulating Tumor Cells - Li, Can; He, Wei; Wang, Nan; Xi, Zhipeng; Deng, Rongrong; Liu, Xiyu; Kang, Ran; Xie, Lin; Liu, Xin (Frontiers in Bioengineering and Biotechnology, 2022)
Tumor metastasis is one of the main causes of cancer incidence and death worldwide. In the process of tumor metastasis, the isolation and analysis of circulating tumor cells (CTCs) plays a crucial role in the early diagnosis and prognosis of cancer patients. Due to the rarity and inherent heterogeneity of CTCs, there is an urgent need for reliable CTCs separation and detection methods in order to obtain valuable information on tumor metastasis and progression from CTCs. Microfluidic technology is increasingly used in various studies of CTCs separation, identification and characterization because of its unique advantages, such as low cost, simple operation, less reagent consumption, miniaturization of the system, rapid detection and accurate control. This paper reviews the research progress of microfluidic technology in CTCs separation and detection in recent years, as well as the potential clinical application of CTCs, looks forward to the application prospect of microfluidic technology in the treatment of tumor metastasis, and briefly discusses the development prospect of microfluidic biosensor.